Biochemical, dielectric and surface characteristics of freeze-dried donkey milk powder - Renu Garhwal; Anuradha Bhardwaj; Harish Kumar; Karnam Sangwan; Ankur Kumari; Bhavya; Manjjri Singal; Varij Nayan; Yash Pal; Tarun Kumar Bhattacharya; B. N. Tripathi (Food and Agricultural Immunology)
Exploration of non-thermal processing methods for milk has garnered attention in the last decade as a potential substitute to traditional thermal procedures. In addition to validating the effectiveness of freeze drying, it is important to evaluate the qualitative attributes of the final product, particularly of dairy products. In current study, freeze-dried donkey milk powder (DMP) was analysed for its Biochemical, Dielectric, functional, Fourier Transform Infrared Spectroscopy and Surface Characteristics. DMP contains notably, high lactose content (62.09%), protein content was determined to be 21.49% with having relatively low-fat content (2.19%). Minerals, amino acid, and fatty acid profiles highlighted nutritional value of DMP. DMP had spherical shape particles with a smooth surface. The FTIR spectra analysis validated the existence of distinct functional groups in DMP. The potential of DMP as a leading candidate for the future of functional food is evident due to its exceptional functional and nutritive properties.